Applicability of land consolidation in a land reform project of Thailand : a case study of the Chao Phraya Irrigated Agriculture Development Project in Ayutthaya Province - Sayan Swangduan; Weber, Karl E.; Routray, Jayant Kumar; Demaine, Harvey; Suvit Yodmani; Canadian International Development Agency (CIDA) (Bangkok : Asian Institute of Technology, 1991)
Land consolidation is the full development of every plot of arable land in order to increase production a nd reduce cost of production, by pooling of several plots of l a nd in t he same area in order to plan n ew land consolidation, irrigation and drainage s y stems, construction of roads or paths for conveyance in the farms, ground levelling, soil maintenance , planning of production and distribution of agricultural products transferring and accepting of l a nd rights a nd such others in connection wit h land consolidation and l a nd allocation for dwelling purposes. Hence, land consolidation should render favorable benefits after the scheme has been implemented. In case of the Chao Phraya Irrigated Agriculture Project, however, some problems emerge from the land consolidation scheme s u c h as controversial issue of l and reallocation, water management problems, high rate of water fee and low crop yield. This study attempts to identify these existing problems as well as farmers' perception to t he project and farmers' views of possible ways to overcome these problems . Various factors have been found out to explain this cover the aspects of social a nd economic, agricultural production, sources and delivery of water and infrastructure development. Findings have shown that the most important constraint is the lack of water to provide to every parcel of land, which may have been t he result of in complete ground levelling and canal construction, inefficiency in the operation and management of the irrigation system. However, l and consolidation render better transportation network a nd better agricultural production. As a result, majority of farmers are satisfied with land consolidation program in this l a nd reform project.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Sciences
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Consolidation of land holdings -- Thailand -- Phra Nakhon Si Ayuthaya